Extracorporeal photopheresis in solid organ transplant–associated acute graft‐versus‐host disease. Issue 4 (18th February 2016) - Houston, Brett L.; Yan, Matthew; Tinckam, Kathryn; Kamel‐Reid, Suzanne; Chang, Hong; Kuo, Kevin H.M.; Tsien, Cynthia; Seftel, Matthew D.; Avitzur, Yaron; Grant, David; Cserti‐Gazdewich, Christine M.
Abstract : BACKGROUND: Extracorporeal photopheresis (ECP) culls pathogenic T lymphocytes, be these the clones of cutaneous T‐cell lymphoma, or mediators of chronic graft‐versus‐host disease (GVHD) after allogeneic bone marrow transplantation (BMT‐GVHD). Whether or not ECP may have an effect in the rarer instances of solid organ transplantation–associated GVHD (SOT‐GVHD) is unclear. Mortality rates in SOT‐GVHD rival those of transfusion‐associated GVHD, with fatalities preceded by pancytopenia and peripheral blood chimerism (PBC) levels exceeding 20%. ECP has been described in two SOT‐GVHD cases to date, with one surviving. STUDY DESIGN AND METHODS: Clinicolaboratory features (including HLA relationships) in a case of multivisceral transplantation were reviewed from the time of surgery to the onset and progression of SOT‐GVHD. ECP, which was introduced as a less immunosuppressive and more selective intervention, was assessed for its effect on serial PBC (as measured by short‐tandem‐repeat analysis) and clinical outcome. RESULTS: Multivisceral SOT‐GVHD manifested with erythroderma, neutropenic sepsis, and PBC increasing from 6% on Posttransplant Day (PTD) 38 to 78% by PTD 60 (at a doubling time of 6 days despite corticosteroids). ECP was administered on PTDs 62 and 67 and was associated with the first evidence of PBC decay to 67% on PTD 69. Death nevertheless ensued on the last day of salvage antithymocyte globulin (PTDs 69‐73) despite further PBC reduction to 41%. CONCLUSION: Further study is needed to determine if the sooner or more frequent application of ECP might attenuate the high case fatality rates of SOT‐GVHD.